Education on Service Standards in Nolokla Village, East Sentani District, Jayapura Regency - Abner Herry Bajari; Dorthea Renyaan; Mesak Rumsowek; Yusuf Gabriel Maniagasi; Jeane K. F. Rumkabu; Semuel Risal (PT FORMOSA CENDEKIA GLOBAL, 2023)
Public service is the provision of goods or services to meet the needs of every citizen based on established service standards. Village officials' understanding of service standards is an important factor, in order to be able to develop service standards that are in line with community expectations. However, many service products still do not yet have service standards, which is a problem in the field, so the community has the right to know the service standards provided. The activities carried out in this community service program are establishing public service standards in Nolokla Village, East Sentani District, Jayapura Regency, by actively involving the community in every stage of activity and providing assistance to village officials to set public service standards. With the dedication of the FISIP campus, Cenderawasih University, Jayapura, regarding Minimum Service Standards (SPM), which are provisions regarding the type and quality of essential services that are Mandatory Government Affairs, every citizen has the right to receive at a minimum. Implementation of SPM starting from the data collection stage, calculating the need to fulfil Basic Services, preparing plans for fulfilling Basic Services and implementing fulfilling Basic Services, and facilitating the preparation of SOPs and Village Head Regulations as a reference for Public Service Standards in Nolokla Village